A Survey on Applications of Nonlinear Data Structures - et. al., C. Padmavathy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, Non-linear data structures and their applications are discussed. Each section in this work provides insights of each non-linear data structure. The types of each non-linear data structure are described along with their applications. This paper provides knowledge about the advantages of employing non-linear data structures in real-time applications.